HUBUNGAN KEPEMIMPINAN KARISMATIK, KEDISIPLINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DP3AP2KB SITUBONDO MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Siri Izzah; Lusiana Tulhusnah; Riska Ayu Pramesthi (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Children are a gift and blessing from God Almighty that must always be maintained. This is because children have dignity and rights as human beings that are inherent in them. In the life of the nation and state, children are the future of the nation and the next generation of the nation's struggle for ideals. Department of Women's Empowerment, Child Protection, Population Control, and Family Planning. The task of DP3AP2KB is to assist the Regent in carrying out government affairs in the field of Women's Empowerment and Child Protection, Population Control, Family Planning (DP3AP2KB). To carry out its duties, DP3AP2KB has functions including formulating policies, implementing policies, implementing evaluations and reporting, implementing administration in accordance with the scope of its duties and implementing other functions given by the Regent related to its duties and functions. The purpose of this study is to analyze and test the Influence of Charismatic Leadership, Discipline and Work Environment on Employee Performance at DP3AP2KB Situbondo Through Job Satisfaction as an Intervening Variable. This research is a quantitative study. The population used in this study was 35 employees other than leaders. The sampling technique used simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Method - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, showed that Charismatic Leadership has a significant positive effect on Job Satisfaction. Discipline has a significant positive effect on Job Satisfaction. The work environment has a positive but insignificant effect on Job Satisfaction. Charismatic Leadership has a positive but insignificant effect on Performance. Discipline has a significant negative effect on Performance. The work environment has a positive but insignificant effect on Performance. Job satisfaction has a significant positive effect on Performance. The results of the indirect influence hypothesis test show that the Charismatic Leadership variable on Performance through Job Satisfaction has a significant positive effect. Discipline on Performance through Job Satisfaction has a significant positive effect. Work environment on Performance through Job Satisfaction has a positive but not significant effect.